Case Report of Granulicatella adiacens as a Cause of Bacterascites - Molly C. Cincotta; K. C. Coffey; Shannon N. Moonah; Dushant Uppal; Molly A. Hughes (Case Reports in Infectious Diseases)
Granulicatella adiacens is a Gram-positive coccus, formerly grouped with nutritionally variant Streptococcus, often found as commensal bacteria of the human oral cavity, urogenital tract, and gastrointestinal tract. Prior case reports have demonstrated Granulicatella spp. as a pathogen that can cause bacteremia and infective endocarditis particularly of prosthetic valves and pacemaker leads. Here, we report on a unique case of Granulicatella adiacens bacterascites in a 50-year-old male.